Positive Potency of Hypothermic Perfusion in Porcine Model of Traumatic Spinal Cord Injury - PapcÃºnovÃ¡, Å tefÃ¡nia; GÃ¡lik, JÃ¡n; Pavel, Jaroslav; ZÃ¡vodskÃ¡, Monika; BimbovÃ¡, KatarÃna; BaÄovÃ¡, MÃ¡ria; FedorovÃ¡, Jana; StropkovskÃ¡, Andrea; KisuckÃ¡, Alexandra; Å ulla, Igor; LedeckÃ½, Valent; LukÃ¡ÄovÃ¡, NadeÅ¾da (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 186